Hydroxyapatite Biomaterials: A Comprehensive Review of their Properties, Structures, Medical Applications, and Fabrication Methods - Kareem, Rebaz Obaid; Bulut, Niyazi; Kaygili, Omer (Sami Publishing Company, 2024)
A researcher needs to know all the chemical, physical, biological, structural, and mechanical characteristics of a biomedical material before using it in medical applications. The mineral hydroxyapatite (HAp, Ca10(PO4)6(OH)2) is an essential component of the calcium orthophosphate family. It possesses great dielectric and biological compatibility properties, diamagnetic properties, thermal stability, osteoconductivity, and bioactivity, which has a Ca:P molar ratio of 1.67. Since HAp has a chemical makeup that is very similar to that of natural bone and teeth, it has the potential to be utilized as a material for the implantation of implants in broken parts of the human skeletal system. Because of the increasing use of HAp in medicine, many methods for producing HAp nanoparticles have been discovered. The preparation conditions of synthesized HAp determine their physical and chemical characteristics, crystalline structure, and shape. This study gives a comprehensive information on the properties and production methods of the HAp in detail and unveile the structure and its properties in detail. © 2024, Sami Publishing Company. All rights reserved.
Keywords: Biomaterials; Biomedical application; Hydroxyapatite; Synthesis methods